2019
DOI: 10.21203/rs.2.10575/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementing a clinical-educator curriculum to enrich internal medicine residents' teaching capacity

Abstract: Introduction Physicians-in-training (residents) are typically the primary educators for medical students during clinical clerkships. However, residents are not formally trained to teach or to assess their teaching. The aim of this study was to assess the implementation of a clinical educator rotation aimed at developing residents’ competencies related to clinical teaching. Methods A mixed-methods approach was used to develop and assess the clinical educator rotation at a teaching community hospital. Internal m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…Moreover, due to the lack of exposure to clinical practice during the theoretical learning stage, it is not possible to apply the relevant skills, which can greatly improve the doctor and nursing students-patient relationship and enable most patients and their families to understand and support clinical internships and internship teaching work. This is very effective in optimizing the clinical teaching environment [11].…”
Section: The Status and Importance Of Doctor And Nursing Students-pat...mentioning
confidence: 99%
“…Moreover, due to the lack of exposure to clinical practice during the theoretical learning stage, it is not possible to apply the relevant skills, which can greatly improve the doctor and nursing students-patient relationship and enable most patients and their families to understand and support clinical internships and internship teaching work. This is very effective in optimizing the clinical teaching environment [11].…”
Section: The Status and Importance Of Doctor And Nursing Students-pat...mentioning
confidence: 99%
“…15 Global research involving a range of health profession training environments has shown that identifying areas of concern can lead to the development of appropriate improvement strategies. 11,16,17 These have included changes to communication and feedback in the CS curriculum, 16 and improved working relationships between the student, CS and educational provider. 17,18 Therefore, gaining insight into the student perspective and satisfaction of learning opportunities within the SVN CLE would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Проаналізовано досвід зарубіжних колег щодо ролі кафедри в медичній освіті , необхідності навчання викладачів закладів медичної освіти (Benor, 2000), методів оцінки програми навчання викладачів (Bockrath, Wright, Uchida, Petrie, 2020;, шляху навчання від студента до викладача в медичній освіті (Chen, et al, 2017;Habboush, Stoner, Torres, Beidas, 2019;Mann, Sutton, Frank, 2007;McKeon et al, 2019), тренінгів підвищення кваліфікації в медичній освіті (Griewatz, Simon, Lammerding-Koeppel, 2017;Soriano, Blatt, Coplit L. et al, 2010), інноваційних методів навчання в медичній освіті (Sadeghi, Heshmati, 2019;Sinclair, Kable, Levett-Jones, 2015;Simpson, Marcdante, Morzinski et al, 2006), особливостей навчання клінічного мислення . У той же час встановлено відсутність комплексних тренінгів підвищення кваліфікації викладачів закладів медичної освіти, з поєднанням дидактичних, клінічних та інноваційних методів навчання.…”
unclassified